Withholding or withdrawing life support in long-term neurointensive care patients: a single-centre, prospective, observational pilot study. Issue 1 (5th May 2020) - Stefanou, Maria-Ioanna; Sulyok, Mihaly; Koehnlein, Martin; Scheibe, Franziska; Fleischmann, Robert; Hoffmann, Sarah; Hotter, Benjamin; Ziemann, Ulf; Meisel, Andreas; Mengel, Annerose Maria
Abstract : Purpose: Scarce evidence exists regarding end-of-life decision (EOLD) in neurocritically ill patients. We investigated the factors associated with EOLD making, including the group and individual characteristics of involved healthcare professionals, in a multiprofessional neurointensive care unit (NICU) setting. Materials and methods: A prospective, observational pilot study was conducted between 2013 and 2014 in a 10-bed NICU. Factors associated with EOLD in long-term neurocritically ill patients were evaluated using an anonymised survey based on a standardised questionnaire. Results: 8 (25%) physicians and 24 (75%) nurses participated in the study by providing their 'treatment decisions' for 14 patients at several time points. EOLD was 'made' 44 (31%) times, while maintenance of life support 98 (69%) times. EOLD patterns were not significantly different between professional groups. The individual characteristics of the professionals (age, gender, religion, personal experience with death of family member and NICU experience) had no significant impact on decisions to forgo or maintain life-sustaining therapy. EOLD was patient-specific (intraclass correlation coefficient: 0.861), with the presence of acute life-threatening disease (OR (95% CI): 18.199 (1.721 to 192.405), p=0.038) and low expected patient quality of life (OR (95% CI): 9.276 (1.131 to 76.099), p=0.016) being significant and independent determinants for withholding or withdrawing life-sustaining treatment. Conclusions: Our findings suggest that EOLD in NICU relies mainly on patient prognosis and not on the characteristics of the healthcare professionals.